THE EFFECT OF WORD SQUARE MODEL ON STUDENTS’ VOCABULARY MASTERY (A Study at The Eleventh Grade Students of SMA Negeri 1 Saipar Dolok Hole) - YENNI KRISNAWATI SIMBOLON (JURNAL LINER (Language Intelligence and Educational Research), 2019)
The purpose of this research is to find: 1)the application of Word Square Model. 2) the extent of the students’ Vocabulary Mastery before and after using Word Square Model. 3) whether there is any significant effect of Word Square Model on students’ Vocabulary Mastery at the Eleventh grade of SMA Negeri 1 Saipar Dolok Hole. Method of the ruler was the experimental. The population of this research was all of the Eleventh grade students of SMA Negeri 1 Saipar Dolok Hole. It consist 144 students. Systematic sampling technique was uses to get a sample it consist 35 students. The technique for collecting data by observation sheet and giving test. The result mean score of the application of Picture Word Inductive Model was 3.30, it was “Very Good”.The result show value before using Word Square Model was 47,24, it was categorized “Fail”. While the mean score of the students’ Vocabulary Mastery after using Word Square Model was 73.72, it was was categorized “Good”. The result of ttest was 4.80 and ttable was 2.04 it means that there is a significant effect of usingWord SquareModel on students’ Vocabulary Masteryat the Eleventh grade students of SMA Negeri 1 Saipar Dolok Hole. Keyword: Word Square Model, Vocabulary Mastery